Impact of Extension Interventions on Capacity Building of Tribal Backyard Poultry Owners in Kandhamal District of Odisha - Singh, D. V.; Jagdev, P. N.; Mohapatra, M. R. (Indian Journal of Extension Education, 2018)
The study investigates the impact of extension interventions on capacity building of tribal backyard poultry owners in  randomly selected six villages of G. Udayagiri and K. Nuagoan blocks of Kandhamal district of Odisha by Random  proportionate sampling (RPS) method. Data were collected through a structured interview schedule from 60 respondent's  (30 from each block) tribal poultry owners by personal interview method and they were analysed using percentage  frequency and chi-square. Suitable extension interventions like group discussion, awareness cum animal health treatment  camps, exposure visits, training programmers were applied in the study areas. The capacity building of poultry owners  were measured on the basis of improvement in knowledge and change in attitude towards scientific poultry farming  practices. The chi-square test was applied 'before' and 'after' interventions of various extension strategies. The study  showed a significant improvement in the knowledge and attitude of tribal poultry owners after extension interventions. It  concluded that the capacity building of poultry owners were increased on the basis of improvement in knowledge and  scientific farming practices.
Keywords: Backyard; capacity building; extension; tribal